Developing a signal-and-system toolbox using GNU Octave - Yang, Yuhang (Nanyang Technological University, 2021)
This dissertation examined the similarities and differences between two software platforms MATLAB and OCTAVE in signal-and-system functions. Although they are both used for scientific calculation in many fields, there still exist some differences in details between them. By comparing the results of tests in signals (including the Fourier transform, Fourier series, power and energy) and systems (including the random variables and autocorrelation), these two software platforms are highly compatible with each other in most cases. However, details in integration functions indicate that MATLAB has more accurate results while OCTAVE may return incorrect answers if the functions for integration are inappropriately employed.